Autologous Skin Fibroblast‐Based PLGA Nanoparticles for Treating Multiorgan Fibrosis. Issue 21 (23rd May 2022) - Long, Qiang; Liu, Zehua; Shao, Qianwen; Shi, Hongpeng; Huang, Shixing; Jiang, Chenyu; Qian, Bei; Zhong, Yiming; He, Xiaojun; Xiang, Xiaogang; Yang, Yang; Li, Bing; et al.
Abstract: Fibrotic diseases remain a substantial health burden with few therapeutic approaches. A hallmark of fibrosis is the aberrant activation and accumulation of myofibroblasts, which is caused by excessive profibrotic cytokines. Conventional anticytokine therapies fail to undergo clinical trials, as simply blocking a single or several antifibrotic cytokines cannot abrogate the profibrotic microenvironment. Here, biomimetic nanoparticles based on autologous skin fibroblasts are customized as decoys to neutralize multiple fibroblast‐targeted cytokines. By fusing the skin fibroblast membrane onto poly(lactic‐ co ‐glycolic) acid cores, these nanoparticles, termed fibroblast membrane‐camouflaged nanoparticles (FNPs), are shown to effectively scavenge various profibrotic cytokines, including transforming growth factor‐ β, interleukin (IL)‐11, IL‐13, and IL‐17, thereby modulating the profibrotic microenvironment. FNPs are sequentially prepared into multiple formulations for different administration routines. As a proof‐of‐concept, in three independent animal models with various organ fibrosis (lung fibrosis, liver fibrosis, and heart fibrosis), FNPs effectively reduce the accumulation of myofibroblasts, and the formation of fibrotic tissue, concomitantly restoring organ function and indicating that FNPs are a potential broad‐spectrum therapy for fibrosis management. Abstract : Fibroblast‐mimicking nanoparticles are developed using autologous skin fibroblast membrane and poly(lactic‐ co ‐glycolic) acid nanoparticles. These biomimetic nanoparticles are shown to effectively scavenge various profibrotic cytokines and reduce the accumulation of myofibroblasts and the formation of fibrotic tissue, concomitantly restoring organ function and indicating their potential as a broad‐spectrum therapy for fibrosis management.